The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.spa.2016.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Modulation equation for SPDEs in unbounded domains with space–time white noise — Linear theory

Abstract: We study the approximation of SPDEs on the whole real line near a change of stability via modulation or amplitude equations, which acts as a replacement for the lack of random invariant manifolds on extended domains. Due to the unboundedness of the underlying domain a whole band of infinitely many eigenfunctions changes stability. Thus we expect not only a slow motion in time, but also a slow spatial modulation of the dominant modes, which is described by the modulation equation.As a first step towards a full … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…Moreover, it would be interesting to extend the present considerations to SPDEs on unbounded domains that are intensely studied over the past few years, cf. [4,11]. Such studies are currently in progress and will be reported in future publications.…”
Section: Conclusion and Future Challengesmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, it would be interesting to extend the present considerations to SPDEs on unbounded domains that are intensely studied over the past few years, cf. [4,11]. Such studies are currently in progress and will be reported in future publications.…”
Section: Conclusion and Future Challengesmentioning
confidence: 84%
“…Models of modulation or amplitude equations [4,12,21,38] have proven to be rather universal and efficient in describing the dynamics associated with a qualitative change of stability (bifurcation). Such structures emerge in fields ranging from spatially and temporarily oscillating wave packets [23] to long waves in dispersive media [36] and spatio-temporal pattern in dissipative systems [31].…”
Section: Introductionmentioning
confidence: 99%
“…The key result towards a full result for amplitude equations on the whole real line with space-time white noise is by Blömker and Bianchi [2]. Here the full approximation result for linear SPDEs, namely the Swift-Hohenberg and Ginzburg-Landau equations without cubic terms, is established.…”
Section: Modulation Equations For Spdesmentioning
confidence: 92%
“…This is a monotone increasing sequence of spaces of continuous functions with growth condition at ±∞ for ̺ > 0. See also Bianchi, Blömker [2].…”
Section: Spacesmentioning
confidence: 99%
See 1 more Smart Citation